Evaluasi Tampilan Antarmuka QGIS dan MapWindow dengan Menggunakan Pendekatan Heuristic Evaluation (Studi Kasus: Fungsi Geoprocessing Tools) - Ramadhan Eka Prana Putera; Fatwa Ramdani; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The quality of the interface in the Geographic Information System (GIS) was still not a major concern, whereas the quality of the interface was the prominent impact on the use of the Geographic Information System and some problems in the interface design contained in the Geographic Information System application were inconvenient to grasp by the user when is compared to the technical problems. This study aims to evaluate the interface of Geographic Information System processing applications (QGIS and MapWindow) so it known that the most optimal interface design could be identified by using the Heuristic Evaluation (HE) method to the function of geoprocessing tools. Based on the evaluation, QGIS application problems in the category "H1 - Visibility of system" and MapWindow application problems in the category "H7 - Flexibility and efficiency of use" were the particular concern for the evaluators. Besides, if the both applications were compared, the earlier evaluation showed QGIS application has 23 problems with an average severity rating is 2.0, this amount was higher compared to MapWindow application which only has 21 problems with an average severity rating is 1.9. However, in the final evaluation showed the different results, QGIS application only has 71 problems with an average severity rating is 2.02, this amount was lower than MapWindow application because the MapWindow application has 73 problems with an average of severity rating is 2.08.